ASSET REDEPLOYMENT, ACQUISITIONS AND CORPORATE STRATEGY IN DECLINING INDUSTRIES - ANAND, JAIDEEP; SINGH, HARBIR (Strategic Management Journal, 1997)
The resource-based perspective suggests that firms are bundles of assets, some of which are fungible in nature. To the extent that some resources are fungible, firms should be able to redeploy them to enter new markets when their existing businesses decline. On the other hand, perspectives that emphasize the business-specific nature of routines or managerial skills point to inherent risks in organizational transformation. In a declining market, resources can be redeployed within the firm through diversification-oriented acquisitions, or they can be redeployed through market mechanisms through consolidation-oriented acquisitions. In this paper, we examine the differences in performance outcomes between diversification-oriented acquisitions and consolidation-oriented acquisitions in industries within the defense sector, which have experienced significant decline. Our results indicate that consolidation-oriented acquisitions outperform diversification-oriented acquisitions in the decline phase of their industries in terms of both ex ante (stock market based) and ex post (operating) performance measures. At the corporate level, we find a positive relationship between focus and Tobin’s q, even when the industry is in decline. The implication of our results is that assets from declining industries are redeployed more effectively through market mechanisms than within the firm through the acquisition of complementary assets. ©1997 by John Wiley & Sons, Ltd.